PENGARUH PENGALAMAN MEREK TERHADAP KESETIAAN MEREK MELALUI KEPUASAN MEREK - Nabilla Devana Adha; Susanta Susanta; Lukmono Hadi (Program Studi Ilmu Administrasi Bisnis, UPN Veteran Yogyakarta, 2021)
This study was conducted to determine the effect of brand experience on brand loyalty through brand satisfaction. The sample size in this study was 69 respondents. The sampling technique used in this research is Non-Probability Sampling with Purposive Sampling for an infinite population. The analysis technique in this study uses descriptive data analysis and inferential statistical analysis using the statistical method of Structural Equation Modeling (SEM) using SmartPLS 3.0. The results of this study conclude that brand experience has a significant effect on brand satisfaction. Brand experience also has a significant effect on brand loyalty, and brand experience has a significant effect on brand loyalty through brand satisfaction. Based on the results of the study, Converse Armada Town Square Magelang should be able to create and improve a positive experience with the Converse brand so that it is expected that there will be satisfaction in the minds of consumers due to the similarity between the performance generated by the Converse brand and consumer expectations regarding the Converse brand. The existence of a positive brand experience and satisfaction in the minds of consumers will then trigger the birth of brand loyalty. Keywords: Brand Experience, Brand Satisfaction, Brand Loyalty.